The Effect of Direct Training and Rope Media Training on Volleyball Underhand Passing Skills at State Vocational School 3 Makassar - Ishak, Muhammad; Sahabuddin, Sahabuddin (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This study aims to examine the effect of direct training and rope media training on students’ underhand passing skills in volleyball at State Vocational School 3 Makassar. The quasi-experimental method was used with a pre-test and post-test design. A total of 30 students were selected through purposive sampling and divided equally into two groups: the direct training group (n = 15) and the rope media training group (n = 15). Each group underwent a six-week intervention, with training conducted three times per week. Data were collected through underhand passing skill tests conducted before and after the training period. The mean pre-test score for the direct training group was 62.4, and the post-test score increased to 75.8, indicating a gain of 13.4 points. Meanwhile, the rope media group showed a pre-test mean of 61.7, which increased to 78.6 in the post-test, with a total improvement of 16.9 points. Statistical analysis using paired sample t-tests showed that both training methods significantly improved the students’ underhand passing skills (p < 0.05). Furthermore, independent sample t-test results revealed that rope media training was significantly more effective than direct training (p < 0.05). In conclusion, both training methods positively impact volleyball underhand passing skills, but rope media training offers a more substantial improvement. These findings suggest that incorporating media such as ropes can enhance learning outcomes in physical education.